Effect of different solar drying methods on quality attributes of dried meat product (kilishi) (2013)
This study was conducted to evaluate the efficiency of four methods of sun drying kilishi after preparation. They included Direct Sun drying Method (DSM) as control, Gujarat Energy Development Agency Method (GEDAM), National Institute of Oceanography Method (NIOM) and Kwatia Drying Method (KDM) each of the methods constituted a treatment viz, A, B, C and D. Meat (Beef) weighing 640 g was purchased and used for this study. The meat was divided into 4 equal parts of 160 g per treatment. They were sliced into length between 0.17 and 0.20 cm in thickness and dried between 4 and 5 hours to reduce the moisture to at least 40% before slurry infusion. The slurry ingredient components were ground and mixed to form a paste. Semi-dried meat were immersed in the slurry for one hour and later stabilized by roasting on charcoal fire for 5 minutes and later dried out in drying media tested in this study. The yield, chemical and sensory properties of kilishi were determined. The results showed that method B gave the highest (P < 0.05) yield of kilishi, chemical attributes as well as sensory properties of kilishi followed by method C. It is suggested that method B and C be developed and produced in commercial quantity for use in drying kilishi in the tropics due to their high efficiency.